(untitled) (Plant Tissue Culture and Biotechnology, 2014)
Silybum marianum is an important medicinal plant used for hepatic disorders. Two varieties exist for this plant S. marianum var. album (white-flowered) and S. marianum var. purple (purple-flowered). A fast and simple method (RAPD) was developed for authentication of S. marianum varieties (purple- and white- flowered) at a DNA level. The two varieties were distinguished by polymorphic bands generated by four decamer primers, namely, OPP-10, OPG-03, OPG-01, and OPC-17. The developed RAPD method will be useful for practical authentication of S. marianum varieties and their adulterants. Plant Tissue Cult. & Biotech. 24(1): 57-63, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19200